Poważna rola niepoważnych rymowanek. Zabawa (gra) słowna w literaturze dla dzieci – jej wartość edukacyjna - Kuszak, Kinga (Studia Edukacyjne, 2020)
The author tackles the subject of children’s literature, described by Jerzy Cieślikowski as “children’s folklore”. Her area of interest centres mainly around poetry addressed to children, which is considered the closest form of literature to this age group. Poetry refers to forms of activity natural for children: rhythmic movement, rhyming, singing, creating new words, asking questions, etc. The article points to the educational role of language games (plays) in poetry, which both answer children’s natural developmental needs and stimulate their linguistic competencies. The first part of the article discusses the sources of language play in poetry. The author highlights the role of the works of Jan Brzechwa and Julian Tuwim, who in the 1930s were the first to employ word play, unconventional use of idioms and proverbs, and nonsensical linguistic associations. They became a source of inspiration for contemporary children’s poets. The paper further analyses selected poems whose common feature is the use of language games not only to entertain but to educate and inspire creativity. The poems were divided into the following categories: poems-plays on sounds (letters), poems- plays on rhyme and rhythm, poems-plays on words, poems-plays on idioms and proverbs, poems-questions and poems-associations. The conclusion points to the role of adults as guides in the world of poetry for children and their role in preparing children to receive and understand the message of poetry.